30.8k views
1 vote
9(m-3)+3m=7m+43 what is the answer

User Cesarbs
by
4.6k points

2 Answers

2 votes

Answer:

m=14

Explanation:

start with your parenthesis and multiply 9 to m-3 which makes that 9m-27+3m=7m+43

add your m together making that 12m-27=7m+43

add 27 to both sides equalling 12m=7m+70

subtract 7m from both sides resulting in 5m=70

divide both sides by 5 equalling m=14

User Guess
by
4.3k points
3 votes

Answer:

9(m - 3) + 3m = 7m + 43

=>9m - 27 + 3m = 7m + 43

=> 12m - 27 - 7m = 43

=> 5m - 27 = 43

=> 5m = 70

=> m = 70/5 = 14

User Pravin Suthar
by
4.5k points